1998
DOI: 10.1086/515042
|View full text |Cite
|
Sign up to set email alerts
|

Successful Medical Therapy for Deeply Invasive Facial Infection Due toPythium insidiosumin a Child

Abstract: Pythiosis occurs in animals and humans who encounter aquatic habitats that harbor Pythium insidiosum. Drug therapy for deeply invasive infections with this organism has been ineffective in humans and animals; patients have been cured only by radical surgical debridement. A 2-year-old boy developed periorbital cellulitis unresponsive to antibiotic and antifungal therapy. The cellulitis extended to the nasopharynx, compromising the airway and necessitating a gastrostomy for feeding. P. insidiosum was isolated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
130
0
3

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(138 citation statements)
references
References 2 publications
5
130
0
3
Order By: Relevance
“…The ocular form of pythiosis is manifest as keratitis that can be severe and result in corneal perforation. The cutaneous and subcutaneous form most often presents as a periorbital cellulitis or mass with progressive local invasion of soft tissue (85,94). The arterial form is the most serious and is largely limited to farmers in Thailand who also suffer from thalassemia (56,75,82,92,100).…”
Section: Unusual Pseudofungal Infectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ocular form of pythiosis is manifest as keratitis that can be severe and result in corneal perforation. The cutaneous and subcutaneous form most often presents as a periorbital cellulitis or mass with progressive local invasion of soft tissue (85,94). The arterial form is the most serious and is largely limited to farmers in Thailand who also suffer from thalassemia (56,75,82,92,100).…”
Section: Unusual Pseudofungal Infectionsmentioning
confidence: 99%
“…Immunodiagnosis using an immunodiffusion or a fluorescent-antibody assay to detect antibodies to P. insidiosum has been useful (75,85). Likewise, the presence of the organism in tissue may be confirmed by staining with specific fluorescentantibody conjugates (57).…”
Section: Unusual Pseudofungal Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be especially problematic in the case of pythiosis because this disease is often confused with those caused by members of the zygomycetes, and this would likely result in the prescription of antifungal agents. Although Shenep et al (48) demonstrated successful synergistic treatment with a combination of itraconazole and terbinafine, therapeutic measures are not expected to have a curative effect since P. insidiosum is not a member of the true fungi and does not respond to common antifungal agents.…”
Section: Vol 42 2004 Species-specific Probe For Pythium Insidiosum mentioning
confidence: 99%
“…Treatment options reported to be successful include supersaturated potassium iodide for the chronic cutaneous form ( 2 ), a combination of terbinafine and itraconazole in a single case of an acute, severe ocular, subcutaneous infection ( 6 ), and therapeutic vaccination for severe infections involving major arteries ( 7 , 8 ) in conjunction with surgery. The first case suggested that, with chronic pythiosis involving the aorta, effective management is difficult.…”
mentioning
confidence: 99%